2024
DOI: 10.1029/2023gl107453
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Gravity Waves on the Thermospheric Circulation and Composition

H.‐L. Liu,
P. H. Lauritzen,
F. Vitt

Abstract: The high‐resolution Whole Atmosphere Community Climate Model with thermosphere/ionosphere extension (WACCM‐X) is used to study the impacts of gravity waves (GWs) on the thermospheric circulation and composition. The resolved GWs are found to propagate anisotropically with stronger eastward components at most altitudes. The dissipation of these waves in the thermosphere produces a net eastward forcing that reaches peak values between 200 and 250 km at mid‐high latitudes in both hemispheres. Consequently, the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Although the current study observed strong EPBs that rose to altitudes over 3,000 km in the western Pacific sector, the EPBs we observed over China only rose to ∼600 km, far lower than the EPBs at over 6,000 km reported by Aa et al (2018) at earlier times. The discrepancy between these observations and model results could be caused by the lack of the prompt penetration field and/or the thermosphere model results being different from actual conditions during the storm (Liu et al, 2024). Future studies will include the prompt penetration electric field by coupling the current model to the Rice Convection Model (RCM) (Toffoletto et al, 2003;Wolf et al, 1991) and to the Comprehensive Inner Magnetosphere-Ionosphere (CIMI) model (Fok et al, 2021); both are currently under development.…”
Section: Discussionmentioning
confidence: 99%
“…Although the current study observed strong EPBs that rose to altitudes over 3,000 km in the western Pacific sector, the EPBs we observed over China only rose to ∼600 km, far lower than the EPBs at over 6,000 km reported by Aa et al (2018) at earlier times. The discrepancy between these observations and model results could be caused by the lack of the prompt penetration field and/or the thermosphere model results being different from actual conditions during the storm (Liu et al, 2024). Future studies will include the prompt penetration electric field by coupling the current model to the Rice Convection Model (RCM) (Toffoletto et al, 2003;Wolf et al, 1991) and to the Comprehensive Inner Magnetosphere-Ionosphere (CIMI) model (Fok et al, 2021); both are currently under development.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, gravity wave activity is strongly dependent on the PV, and it acts to modulate the effectiveness of gravity wave propagation into the mesosphere thermosphere as well as generate secondary gravity waves (Harvey et al, 2022) Modulations in the strength of the PV should therefore also be expected to induce perturbations in residual thermospheric circulation via gravity waves, which would also be reflected in the global distribution of O/N 2 . Recently, Liu et al (2024) used a high resolution version of WACCM-X to demonstrate that forcing from relatively small scale gravity waves, which are not presented in the standard version of SD-WACCM-X used here, impact circulation in the lower thermosphere and the ratio of O/N 2 . A study of the relative contributions of gravity wave, tidal, and planetary wave activity to residual circulation (and O/N 2 ) variance during anomalous PV times would, therefore, require a version of WACCM-X capable of resolving gravity waves, and is therefore left as a goal for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the tidal amplitudes are mostly overestimated in the WACCM-X model simulations, the forcing by smaller-scale gravity waves is thus not sufficient in the model. Impacts of gravity waves have been demonstrated using high resolution WACCM-X simulations (H.-L. Liu et al, 2024). These waves can effectively modify the general circulation in the thermosphere.…”
Section: Annual and Semiannual Variationmentioning
confidence: 99%